NGHIÊN CỨU TỔNG HỢP SÉT CHỐNG NHÔM HỮU CƠ VÀ KHẢ NĂNG HẤP PHỤ PHẨM NHUỘM ANION CỦA CHÚNG TRONG NƯỚC - Đức, Trương Đình; Bằng, Nguyễn Văn (Vietnam Journal of Chemistry, 2012)
Clays have played a major role in human life. Clays are used and their value recognized in many economic branches, agriculture, civil engineering and environmental studies etc. This is largely because of their wide-ranging properties, high resistance to atmospheric conditions, geochemical purity, high surface area, easy access to their deposits near the earth’s surface and low price [1]. In environmental treatment, clays were usually refined and then modified to improve their adsorption capacity [2 - 4]. In this research, bentonite clay from Di Linh (Lam Dong, Vietnam) was used for pillaring process after refining. Keggin ions were synthesized through chemical reaction of AlCl3.6H2O/NaOH solutions. Aluminum pillared clay (Al-PILC) was prepared by contacting of Keggin ions and Na-montmorillonite (MONT-Na) aqueous suspension with different ratios. Al-PILCs were then modified by cethyltrimethylammonium bromide (CTAB). The obtained materials were characterized by XRD, IR, DTA-TGA, SEM, TEM, BET and 27Al-MAS-NMR methods. Their adsorption capacity was investigated with methyl orange (MO) from aqueous solution at pH 7.0 and controlled temperature 298±0.20 K. The obtained results demonstrate that the adsorption capacity of 7.5 and 10.0 Al-PICL-CTAB samples were highest